Australian Football League concussion guidelines: what do community players think?. Issue 1 (28th November 2016) - White, Peta E; Donaldson, Alex; Sullivan, S John; Newton, Joshua; Finch, Caroline F
Abstract : Background: Preventing concussion in sport is a global challenge. To assess community-level adult male Australian Football players' views on following the Australian Football League's (AFL) concussion guidelines. Methods: 3 focus groups, each comprising 6 players from 1 regional league, were conducted until saturation of issues raised. Discussions followed a semistructured script and were audio-recorded and transcribed verbatim. Thematic analysis was conducted by 2 coders independently. Results: Identified advantages of the guidelines included highlighting the seriousness of concussion; changing the culture around playing with concussion and shifting return-to-play decision responsibility from players to others. Disadvantages included players being removed from play unnecessarily; removal of players' rights to decide if they are fit to play and players changing their behaviours to avoid being removed from play. Identified facilitators to guideline use included local league enforcement; broad information dissemination and impartial medically trained staff to assess concussion. Identified barriers to guideline use included players' desire to play at all costs; external pressure that encouraged players to return to play prematurely; and inconvenience and cost. Conclusions: Players generally understand that the AFL concussion guidelines protect their long-term welfare. However, their desire to play at all costs and help their team win is a common barrier to reporting concussion and adhering to guidelines. Leagues should take a lead role by mandating and enforcing the use of the guidelines and educating coaches, game day medical providers and players. The return-to-play component of the guidelines is complex and needs further consideration in the context of community sport.